Association between lung capacity measurements and abnormal glucose metabolism: findings from the Crossroads study. Issue 5 (18th November 2013) - Yu, D.; Simmons, D.
Abstract Aim To examine the association between lung function and metabolic syndrome/Type 2 diabetes. Methods A total of 1454 adults from rural Victoria, Australia, from randomly selected households included in the Crossroads study, provided spirometric measurements including forced vital capacity, forced expiratory volume in 1 s, predicted percentage value of forced expiratory volume in 1 s and forced vital capacity predicted percentage value. Assessments also included HbA1c, metabolic syndrome components and a 75‐g oral glucose tolerance test. The area under the receiver‐operating characteristic curves for waist circumference were compared with those for combinations of waist circumference and raw spirometric measures (forced vital capacity and forced expiratory volume in 1 s) for identifying metabolic syndrome or Type 2 diabetes. Results Partipants with a greater number of metabolic syndrome components were more likely to have reduced lung function, particularly if Type 2 diabetes was present: the predicted value of forced expiratory volume in 1 s decreased by 5–6% for participants with 2–4 metabolic syndrome components, and by 9% for those with Type 2 diabetes. The risk of metabolic syndrome or Type 2 diabetes was inversely associated with higher spirometry values (forced expiratory volume in 1 s percentage predicted value: odds ratio for 2–4 metabolic syndrome components 0.36–0.21 in women and 0.32–0.30 men; the odds ratio for Type 2 diabetes was 0.36 in women and 0.28 in men). Receiver‐operating characteristic curve analysis for identifying metabolic syndrome and Type 2 diabetes revealed significant differences between the area under the receiver‐operating characteristic curve with waist circumference alone and that for the combination of waist circumference with lung capacity measures. Conclusion Pulmonary function is lower in people with metabolic syndrome and Type 2 diabetes. Spirometry variables are independent predictors of metabolic syndrome and Type 2 diabetes.